MODEL PEMBELAJARAN PAIR CHECK TERHADAP KEMAMPUAN MENULIS TEKS PROSEDUR PADA SISWA KELAS IV SD - Lintang Aulia Nafilah; Ira Eko Retnosari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Many elementary students still struggle to write procedure texts due to limited experience, making them unfamiliar with appropriate text structures and formats. Additionally, the use of less effective learning models contributes to their inability to produce grammatically correct and well-structured texts to clearly convey procedures. This research aims to examine the impact of the Pair Check learning model on fourth-grade students’ ability to write procedure texts. The study employed a quasi-experimental method with a non-equivalent pretest-posttest control group design. The population consisted of fourth-grade students at SDN Dukuh Menanggal 01/424 Surabaya, with 49 students from classes IV A and IV B selected through purposive sampling. Data were collected via pretests and posttests, then analyzed using an independent samples t-test. The results revealed a significant influence of the Pair Check model on students' writing skills, supported by a p-value of 0.000 (<0.05). Furthermore, the experimental class showed an increase in the average score from 41 (pretest) to 53.57 (posttest), marking a 12.57-point improvement.